Bio-waste orange peel and polymer hybrid for efficient energy harvesting. (November 2020) - Gaur, Anupama; Tiwari, Shivam; Kumar, Chandan; Maiti, Pralay
Abstract: Bio-waste orange peel with poly(vinylidene fluoride) hybrids have been developed as an efficient energy harvester. Bio-wastes in huge amount cause landfills and environmental pollution. An effort in the direction of using bio-waste will be beneficial in many ways. Orange peel, a bio-waste, is mainly composed of cellulose and different proteins that are responsible for its piezoelectric effect. The hybrid exhibits significant piezoelectric properties arising through induced piezoelectricity in the polymer matrix by the smaller dimension orange peel powder as filler causing an electroactive phase of ∼ 70% in the hybrid. Integrated device has been fabricated for energy harvesting using the hybrid material, without conventional high voltage poling, which displays very high open circuit voltage of ∼ 90 V and power of 135 μ W/cm 2 using finger tapping. The hybrid nanogenerator is proficient in light up the LEDs from the movement of sliding door and from any human body movements like bending, twisting and walking etc. The underlying mechanism of enhanced piezoelectricity in the hybrid is revealed through structure, morphology and thermal studies of the hybrid. Thus, the piezoelectric energy harvester prepared from the bio-waste might be one of the solutions to utilize the bio-waste. Graphical abstract: Highlights: Bio-waste (orange peel) hybrid is used as nanogenerator. Easy processable but tough polymeric matrix is able to convert into piezoelectric form. Very high conversion efficiency has been reported with 90 V output with 135 μ W/cm 2 power generation density. Structural and morphological reason responsible for this huge improvement has been revealed.